Effect of asymmetric fluid flow distribution on flow boiling in a microchannel heat sink – An experimental investigation. (August 2022) - Kumar, Ritunesh; Singh, Gurjeet; Mikielewicz, Dariusz
Highlights: Effect of flow maldistribution during subcooled flow boiling in MCHS is studied. Boiling incepted at different heat flux in central and side microchannels. Downstream flow compressibility is even observed during boiling process. Boiling incepted in central microchannel under influence of mirage vapor core. Temperature non-uniformity increases in the traverse direction during flow boiling. Abstract: Flow boiling in microchannels is emerging as an exclusive cooling solution for miniaturized high-power electronic devices alongside having other high heat flux applications. Size miniaturization at microscale strangely increases heat transfer performance as well as flow boiling instabilities. Many flow boiling instabilities are interrelated and result from imperfect hydrodynamic conditions. One of such problems is flow maldistribution among parallel channels of a microchannel heat sink. Very limited studies have dedicatedly investigated the negative effects of flow maldistribution on the boiling process in microchannels. A microchannel heat sink with twenty-five rectangular microchannels (width × height × length = 0.45 × 0.725 × 25 mm) made on a copper block base of 25 × 25 × 85 mm using wire electrical discharge machining under an I-type flow configuration is investigated for that purpose. Flow boiling patterns of central and side microchannels as well as the temperature profile of central and side microchannels are recorded. The boiling process always incepts in side microchannels and rapidly converts into a periodic flow reversal up to the inlet manifold, whereas weak, stable, bubbly flow and single-phase liquid flow are observed in the neighboring and central microchannels, respectively. Furthermore, with the increase of heat flux, flow boiling intensity increases and more parallel microchannels start experiencing rapid bubble growth; consequently, the intensity of flow reversal in side channels also increases. At high heat fluxes, the vapor backflow of side microchannels reaches the central microchannel and blocks the flow through it, named mirage flow confinement. Boiling in the central channel aggravates under the influence of the mirage flow reversal processes. Temperature non-uniformity across the microchannel heat sink increases with the increase of heat flux and mass flux caused by the early appearance of a partial dryout of side channels and the escalation of the flow distribution asymmetry. Whereas, better temperature distribution is observed at higher inlet fluid temperatures.